Attitude as A Variable between the Effect of Security, Cleanliness and Public Facilities on Domicile Decisions in Satelit City of Sidoarjo District - Abdul Halik (STKIP Singkawang, 2019)
Satelit city has populations mostly working in metropolitan cities. Migration from metropolitan cities to Satelit city due to the land use reduction and the house purchasing power has increased, while the residence needs are very important. Workers in metropolitan cities drive off through traffic jam. Students go to metropolitan cities from the Satelit city looking for better education facilities. The population density in Satelit city is caused by migration from metropolitan cities. Migration is the occurrence of sub-urbanization phenomena in a Satelit city around the city of Surabaya. The development of Satelit city is very dynamic and making people try to find a more comfortable place and friendly neighborhood. Property developers have provided the concept of a convincing residence which is conducive, clean and safe so that the decision to domicile to live in Satelit city more commodious.The security of a city influences a person's attitude in determining a place to live. A safe environment will make residents save. Security of family, wealth and place is a necessity that must be fulfilled in order to live a happy life. Moreover, the aspect that influences the attitude of people's domicile decisions is the cleanliness of the city. Cleanliness is related to the elements of health, pollution, and odor, so as the ideal place to live in is a place which is free from all factors that interfere with human health. Many developers organize neatly locations, a human lifestyle based on the rules of the developers, so that cleanliness can be controlled properly. With adequate facilities, residents will stay in Satelit city and not go to big cities. Public facilities will strengthen the attitude of a person to live in a Satelit city if the needs of citizens are fulfilled. The sense of security that is needed for the residents is the security of the neighborhood in which they live in because each person realizes that security is often unexpectedly disturbed. The cleanliness aspect is not an absolute requirement, because the clean and beautiful city is common. Deciding to stay in a place, the public facilities need to be seriously considered, because every person has the pretension to live and settle down. As a result of the data analysis and discussion on various variables and indicators, the researcher suggests that (a) for domiciles in Satelit city, someone must consider the public facilities available. Many elements become alternatives for them and can ensure that forming a family is more comfortable and saver (b) developers can provide residences accordance with purchasing power and setting security, cleanliness, and facilities as well as those needed by residents. A sense of security, cleanliness and reachable facilities will strengthen a person's decision to choose to live in a certain area.